Early hydration-retarding mechanism of polymer-modified cement. (November 2015) - Kang, S.; Kim, J.; Moon, C.; Song, M.
Abstract : Polymers added to cement to enhance its physical properties can retard its hydration reaction and actually reduce its compressive strength. The mechanism of this retardation in cement composites containing ethylene–vinyl acetate was, therefore, investigated by evaluating the viscosity, heat of hydration, setting time and Ca 2+ ion leaching with various ratios of polymer to cement. It is found that increasing the amount of polymer caused a decrease in Ca 2+ ion leaching owing to an increase in viscosity, and that this delayed hydration. Furthermore, the hydration process hydrolysed the vinyl acetate in ethylene–vinyl acetate, producing acetate ions that react with Ca 2+ to form calcium acetate. As this reaction consumed Ca 2+ ions, it created unreacted sulphate ions that further delayed the hydration reaction. It is these two factors that are considered to be the main cause for the delayed hydration reaction observed in cement–polymer composites.